THE EFFECT OF AMBIENT RELAXATION MUSIC ON ANXIETY OF PROSPECTIVE IMPLANT KB ACCEPTORS AT TPMB ELLA WIYASA PUTRI INDAHWAN KROMENGAN DISTRICT, MALANG : AMBIENT RELAXATION MUSIC - Wika Ariani; Rosyidah Alfitri; Tut Rayani Aksohini Wijayanti (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2026)
Background: Background: Anxiety is response common psychological experienced candidate acceptor birth control implant before procedure installation, which can influence readiness, comfort, and acceptance to Action. One non-pharmacological method that can be applied to address this problem is ambient relaxation music, which has gentle and soothing properties. This study aims to evaluate the impact of relaxation using ambient music on anxiety in prospective contraceptive implant recipients. Methods: Study This use design pre-experimental one group pretest- posttest on 30 respondents with purposive sampling. Anxiety measured before and after intervention music 20 minutes of ambient relaxation using HARS. Results: The pretest results showed 60.0% (18 respondents) were anxious mild, 26.7% (8 respondents) moderate, and 13.3% (4 respondents) severe. After intervention, occurs change to 16.7% (5 respondents) no anxious, 46.7% (14 respondents) mild, and 36.7% (11 respondents) moderate. The Wilcoxon test shows difference significant (Z = -2.887; p = 0.004), confirming effectiveness music deep ambient relaxation lower anxiety candidate implant contraceptive acceptor as well as potential as intervention simple, safe, and applicable non- pharmacological in service midwifery. Conclusion: relaxation using ambient music has significant effect on reduction of anxiety candidate implant contraceptive acceptor.